Visual Indicator Based on Leuco Crystal Violet for Radiation Processing Technology - Shinde, Santosh Harsichandra; Mondal, Suvendu; Sathian, Vilippalil (IPTEK The Journal for Technology and Science, 2019)
One of the important technologies for food preservation and processing is radiation processing, which is growing at ever increasing rate in India. Efforts are being done to make it more cost-effective, so there is always a need for cost-effective, indigenously developed visual indicators for providing an easy identification and segregation of irradiated products. Thus development of cost-effective visual indicator based on leuco crystal violet for doses â‰¥ 10 kGy was under taken. Current research works deals with fabrication and characterization of various parameters such as optimum composition, light stability, temperature effect and effect of relative humidity on the new indicator.